Pengaturan Pelaksanaan Putusan Ajudikasi Non-Litigasi Sengketa Informasi Publik Oleh Komisi Informasi Provinsi Jawa Tengah - Devanno Arya Candra; Waluyo Waluyo; Abdul Kadir Jaelani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to examine the problems, First see whether the implementation of non-litigation adjudication decisions on public information disputes in Central Java Province has been implemented.Second,what are the obstacles and efforts made in fulfilling the right to information in order to achieve the mandate of the 1945 Constitution Article 28F. This research is empirical legal research with a qualitative approach. Types and sources of data include primary data and secondary data. The data collection technique used was interviews with the Commissioner of the Central Information Commission and the Assistant Commissioner of the Central Java Province Information Commission, then the data analysis technique used was qualitative. The research results show thatFirst,non-litigation adjudication decisions have not been implemented due to several factors, namely the weakness of the trial procedural law regulated in the Information Commission Regulation (PERKI), the absence of authority given to the Information Commission in overseeing decisions, and the independence of the Information Commission which is still very dependent on each commissioner. The obstacles that exist at the Central Java KIP in implementing non-litigation adjudication decisions, namely the legal substance related to the weakness of the PERKI as well as the urgency of revising the KIP Law in safeguarding community dynamism, the legal structure related to the limited budget owned by the Central Java KIP and the limited number of Information Commission employees who do not followed by an increase in quality, as well as community culture regarding the number of applicants who are not serious.